2013
DOI: 10.1111/psyp.12036
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and pain sensitivity in children and adolescents

Abstract: Elevated blood pressure is associated with diminished pain sensitivity. While this finding is well established in adults, it is less clear when the relation between blood pressure and pain sensitivity emerges across the life course. Evidence suggests this phenomenon may exist during childhood. Children (N = 309; 56% boys) aged 10–15 years and their parents participated. Blood pressure readings were taken during a resting baseline. Maximum pain intensity was rated using a visual analogue scale (rated 0–10) in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
3
4
0
Order By: Relevance
“…Cut‐off points for disease chronicity giving the best‐fitting models showed that after the collapse of the purported “pain resilience” mechanism, longer disease duration transferred decompensated physiological regulation to two independent mechanisms interpreted as adaptation to or aggravation of chronic pain severity through sustained elevation in BP or through affective comorbidity (higher negative affect), respectively. Considerations of high BP as an indicator of adaptation (“pain killing”) mechanism and high negative affect as an indicator of aggravation mechanism in this chronic pain syndrome are consistent with other studies . The associations between longer disease duration and greater systolic BP and between longer disease duration and higher negative affect were found to be mediated by the same shifting of the BP start point for baroreceptor activation to a higher value (ie, resetting baroreceptor activation).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Cut‐off points for disease chronicity giving the best‐fitting models showed that after the collapse of the purported “pain resilience” mechanism, longer disease duration transferred decompensated physiological regulation to two independent mechanisms interpreted as adaptation to or aggravation of chronic pain severity through sustained elevation in BP or through affective comorbidity (higher negative affect), respectively. Considerations of high BP as an indicator of adaptation (“pain killing”) mechanism and high negative affect as an indicator of aggravation mechanism in this chronic pain syndrome are consistent with other studies . The associations between longer disease duration and greater systolic BP and between longer disease duration and higher negative affect were found to be mediated by the same shifting of the BP start point for baroreceptor activation to a higher value (ie, resetting baroreceptor activation).…”
Section: Discussionsupporting
confidence: 88%
“…Its adaptive attribute is concordant with findings of increased upright BP level as a biomarker of a more universal mechanism of adaptation to negative affect and chronic pain severity. 68,72 Other findings of the study confirm a prediction that in the sample of IBS patients, greater chronicity and severity of pain and usual IBS symptoms are related to decreased power of the high-frequency band of HRV at rest coupled with increased negative affect (the putative "pain aggravation" mechanism identified as an affective component or comorbidity of the disease). It corresponds with the findings indicating association of reduced HRV with both severe abdominal pain 19 and higher negative affect 21 in women with IBS.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Considering all these pros and cons, we are always looking for safer alternative analgesia techniques in our daily practice of anesthesia. In this regard, the relationship between high arterial blood pressure and reduced sensitivity to pain has been studied and proved in several investigations (29)(30)(31)(32). Therefore, the relationship between pain and hypertension is of great pathophysiological and clinical interest in the field of pain management.…”
Section: Introductionmentioning
confidence: 99%